THE PHENOMENON OF JULIET’S WALL IN THE MOVIE LETTERS TO JULIET - LESTARI, AYU MIRANTI PUJI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Miranti, Ayu. 2014. “The Phenomenon of Juliet’s Wall in the Movie  Letters to Juliet”. Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies, Universitas Brawijaya.Supervisor: Sri Utami Budi; Co-Supervisor: Aris Siswanti.Keyword: phenomenon, Juliet’s Wall, social group, interaction.Society has tradition in share culture as human social behavior. Social phenomena can spread widely because of society behavior in share culture each other. Society in sharing culture influence and influenced by past generation and social group members. Further, the way society share culture is by social interaction between them. In the movie entitled Letters to Juliet  portrayed  the phenomenon of Juliet’s Wall. It tells about the writing letters phenomenon in Verona, where the story Romeo and Juliet took place. There are some women writing the answer for people who put their letter in Juliet’s Wall as Juliet named Secretaries of Juliet. This phenomenon spread belief of the power of true love and hopes for people who write the letter. Observing the Juliet’s Wall phenomenon will be the main problem in this study. Sociological approach is applied in conducting this study. Since movie is used as material object, movie studies will be applied as supporting approach. This study finds that Juliet is symbolized as the internal symbol of love. People believes in Juliet are because of they looking for a way to unburden their feeling, to share their problems with someone who will listen, unconditionally, as if she were a friend, or confidante. Further, people see Juliet as a legend, someone who has tragic love story written by Shakespeare. From  that point of view people generally think that it is worth if they have “direct contact” with Juliet in order to be part of a legend. Further, social interaction and society behavior in sharing culture each other can make Juliet’s Wall phenomenon alive. People who believe in Juliet’s Wall are the people who believe in the existence of true love. Juliet’s Wall make everyone who writes the letter believe that true love is really exist and drive them to struggling for their love.